Work Tenure and Attitude Associated with Unsafe Action Among Workers at “X Company”, Indonesia - Putri Taufiq, Susan Nabila; Pasca Budiono, Nugrahadi Dwi; Pradhana, Andrea Thrisiawan (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: The incidence of unsafe behavior has increased over the last three years. This was based on the incidence of minor work accidents and findings of near-miss conditions in each production area. This research aimed to analyze the association between age, tenure, and work attitude on unsafe action among “X company” workers.Methods: This study employed a quantitative analytical method with a cross-sectional design. The population in this study comprised of 93 workers in the production area of “X Company” in one of the plants. A simple random sampling technique was used, which yielded a sample size of 76 respondents. The independent variables studied were age, work tenure, and work attitude. The dependent variable was unsafe action. Data were collected through interviews using questionnaires, which had been tested for their validity and reliability. Chi-square tests and multiple logistic regressions were used for data analysis.Results: The subjects were between 25-56 years, with an average of 41.2 years. The majority of the subjects (85.5%) had work tenure for ≥ 10 years, 67.1% had negative work attitude, and 53.9% had unsafe action. There was no association between age and unsafe action (p=1.000), but there were associations between work tenure (0.004) and work attitude (p=0.0001) with unsafe action. The multiple logistic regression showed that both work tenure and attitude concurrently associated to unsafe action.Conclusion: The work tenure of more than ten years and negative work attitude were associated to unsafe action behavior in “X Company,” whereas age did not associated to unsafe behavior.